2019
DOI: 10.1096/fj.201900531rr
|View full text |Cite
|
Sign up to set email alerts
|

Corin plays a protective role via upregulating MAPK and downregulating eNOS in diabetic nephropathy endothelial dysfunction

Abstract: Diabetic nephropathy (DN) is one of the leading causes of mortality in diabetic patients, but its pathogenesis is unclear. We aimed to study the role of the pro-ANP convertase Corin in the pathogenesis of DN. Corin and ANP expression in DN rat kidneys and high-glucose-treated HK-2 cells was analyzed by real-time PCR, western blotting, and immunohistochemical staining. The effect of Corin-siRNA or ANP-siRNA HK-2 cells on EA.hy926 cell migration was determined by scratch-wound healing assay. The expression of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Synthesized as a zymogen, corin needs to be cleaved by a proprotein convertase subtilisin/kexin-6 (PCSK6, also called PACE4) in order to be activated ( Chen et al, 2018 ). The kidney is the second organ with the highest amount of corin after the heart ( Xue et al, 2020 ). Corin expression has been detected in the proximal tubule, the distal tubule (largely in the thick ascending medullary loop), and the collecting duct (especially in the internal medullary collector duct; Theilig and Wu, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Synthesized as a zymogen, corin needs to be cleaved by a proprotein convertase subtilisin/kexin-6 (PCSK6, also called PACE4) in order to be activated ( Chen et al, 2018 ). The kidney is the second organ with the highest amount of corin after the heart ( Xue et al, 2020 ). Corin expression has been detected in the proximal tubule, the distal tubule (largely in the thick ascending medullary loop), and the collecting duct (especially in the internal medullary collector duct; Theilig and Wu, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…3A ) revealed that the expression of APJ in the renal tissues of rats was decreased after the apelin-13 injection at 8 weeks compared with that at 3 weeks. NO production could relieve the diabetic nephropathy-induced vascular damage in the renal tissue ( 21 ). Therefore, the production of NO, Ang II and ET-1 was detected in the renal tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Diabetes mellitus usually causes microangiopathy, which in turn leads to chronic progressive lesions, hypofunction and failure of tissues and organs such as eyes, kidneys, nerves, heart and blood vessels. It has been shown that the IL-33/ST2 signaling pathway is activated in diabetic nephropathy ( Elsherbiny et al, 2020 ), and endothelial dysfunction can be induced during the development of diabetic nephropathy ( Xue et al, 2020 ). Interestingly, ST2, the key protein in this study, can be produced by endothelial cells, which activate immune responses and trigger organismal protective mechanisms by expressing large amounts of ST2 during the sepsis process ( Huang et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%